Statistical optimization for the production of recombinant cold-adapted superoxide dismutase in E. coli using response surface methodology. Issue 6 (2nd November 2017) - Wang, Yatong; Wang, Quanfu; Wang, Yifan; Han, Han; Hou, Yanhua; Shi, Yonglei
ABSTRACT: Cold-adapted superoxide dismutase (SOD) with higher catalytic activity at lower temperature has great amount of applications in many aspects as an industrial enzyme. The application of recombinant enzyme in gene engineering and microbial fermentation technology is an effective way to obtain high-yield product. In this study, to obtain the recombinant SOD in E. coli ( rPs SOD) with the highest activity, the Box-Behnken design was first applied to optimize the important parameters (lactose, tryptone and Tween-80) affecting the activity of r Ps SOD. The results showed that the optimal fermentation conditions were Tween-80 (0.047%), tryptone (6.16 g/L), lactose (11.38 g/L). The activity of rPs SOD was 71.86 U/mg (1.54 times) as compared with non-optimized conditions. Such an improved production will facilitate the application of the cold-adapted rPs SOD.